Comparison of the expression of neurotransmitter and muscular genesis markers in the postnatal male mouse masseter and trigeminal ganglion during development. Issue 6 (19th December 2017) - Kamata, Hiroaki; Karibe, Hiroyuki; Sato, Iwao
Abstract: Calcitonin gene–related peptide (CGRP) is released by motor neurons and affects skeletal muscle fiber and transient receptor potential cation channel subfamily V member 1 (TRPV1), an important marker of pain modulation. However, the expression of CGRP and TRPV1 in the trigeminal ganglion (TG) during changes and in feeding patterns has not been described. We used real‐time reverse transcription polymerase chain reaction and in situ hybridization to investigate the mRNA expression levels of CGRP and TRPV1 in the TG. The expression of myosin heavy‐chain (MyHC) isoforms was also investigated in the masseter muscle (MM) during the transition from sucking to mastication, an important functional trigger for muscle. The mRNA and protein levels of CGRP increased in the MM and TG from postnatal day 10 (P10) to P20 in male mice. The protein levels of TRPV1 were almost constant in the TG from P10 to P20, in contrast to increases in the MM. The mRNA abundance of TRPV1 in the TG and MM was increased from P10 to P20. The localization of an antisense probe was used to count CGRP cell numbers and found to differentiate the ophthalmic, maxillary, and mandibular nerve divisions of the TG. In particular, the number of CGRP + cells per 10, 000 μm 2 in the maxillary and mandibular divisions of the TG gradually changed from P10 to P20. The expression of CGRP and TRPV1 in the TG and MM and the patterns of expression of different MyHC isoforms were affected by changes in feeding during male mouse development. Abstract : The expression of detected mRNA CGRP and TRPV1 was found in trigeminal ganglion serial sagittal sections using in situ hybridization obtained from mice at postnatal day 10 (P10) to P20. The TG sagittal sections were hybridized with an antisense (CGRP: a, c, e; TRPV1: g, i, k) or sense (CGRP: b, d, f; TRPV1: h, j, l) probe. The boxes (1–6) outlined in panels a, c, e, g, i, and k are shown at high magnification in panels m–r, as follows: m (box 1, see panel a), n (box 2, see panel c), o (box 3, see panel e), p (box 4, see Figure5 g), q (box 5, see panel i), and r (box 6, see panel k). a, b, g, h, m, p: P10; c, d, i, j, n, q: P15; and e, f, k, l, o, r: P20. Weakly positive cell (black arrowheads, panel r‐a), moderately positive cell (black arrowheads, panel r‐b), and strongly positive cell (white arrows, panel r‐c). ant = anterior; post = posterior; d = dorsal; v = ventral. a–r: bar = 100 μm. r‐a‐c, 10 μm.